New Tendencies in the Economic Dynamics of the European Union - Pirimova, Vera (Research Papers, 2012)
In the present scientific paper are deduced basic characteristics and new tendencies in the cyclic recurrence of the economic dynamics of the European Union. The analysis ascertain raising hardiness of the European Union economy to cyclical fluctuations and impacts and is described a tendency toward considerable change in the character of the cyclical development on regional level. It finds expression in a gradual transition from the traditional cyclic recurrence in the form of economic cycle to a new cyclic recurrence in a form of economic growth cycles. As a major internal and external determinants of this change have revealed the alteration in the type of the economic system and the outlined new leading economic sectors, the increasing trade and finance openness of the European countries economies.The European Union economic dynamic take shape under the crucial impact of specific national peculiarities, what are disclosed by separating of 3 groups states in EU according to the GDP per capita level (in PPS). Special contribution to the general tendencies in EU have the countries from the Central and Eastern Europe in view of the realized transition to market economy and the development of specific transformational cycle. These processes contribute to greatest internal (regional) cyclical resistibility of the European Union economy, to moderate the parameters and expressions of the basic cyclical indicators.